2012
DOI: 10.1016/j.ceb.2012.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lipid metabolism: a tale of two yeasts

Abstract: Eukaryotic cells synthesize multiple classes of lipids by distinct metabolic pathways in order to generate membranes with optimal physical and chemical properties. As a result, complex regulatory networks are required in all organisms to maintain lipid and membrane homeostasis as well as to rapidly and efficiently respond to cellular stress. The unicellular nature of yeast makes it particularly vulnerable to environmental stress and yeast has evolved elaborate signaling pathways to maintain lipid homeostasis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 70 publications
1
25
0
Order By: Relevance
“…The expression of lipid synthesis may also be directly regulated by SREBP/Upc2 [e.g., in C. neoformans (27) and in S. pombe (62)] or other transcription factors [e.g., Efg1 in C. albicans (119)]. However, it is likely that other mechanisms, such as a general stress response, are also involved (108).…”
Section: Regulation Of Sterol Lipid and Iron Metabolism Genesmentioning
confidence: 98%
See 1 more Smart Citation
“…The expression of lipid synthesis may also be directly regulated by SREBP/Upc2 [e.g., in C. neoformans (27) and in S. pombe (62)] or other transcription factors [e.g., Efg1 in C. albicans (119)]. However, it is likely that other mechanisms, such as a general stress response, are also involved (108).…”
Section: Regulation Of Sterol Lipid and Iron Metabolism Genesmentioning
confidence: 98%
“…For example, in A. fumigatus, the expression of genes required for the early steps in ergosterol synthesis (terpenoid synthesis) is reduced in hypoxia, leading to a decrease in substrates such as mevalonate. Barker et al (9) have suggested that there may be a direct link between hypoxic regulation of terpenoid biosynthesis and ergosterol synthesis that bypasses direct regulation by SREBP, possibly by acting through HMG-CoA reductase (108).…”
Section: Regulation Of Sterol Lipid and Iron Metabolism Genesmentioning
confidence: 98%
“…Proteostasis pathways have been around since the dawn of proteins, and evolution has apparently capitalized on the specificity and alacrity of these mechanisms in many facets of sterol regulation. Our review is not comprehensive, but fortunately many current examples exist (Brown & Goldstein 2008, Jiang & Song 2014, Jo & DeBose-Boyd 2010, Raychaudhuri et al 2012, Sharpe et al 2014, Ye & DeBose-Boyd 2011, Zhang et al 2012). This review tells a particular set of stories about using protein quality control to regulate metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The transcriptional regulation in mammals relies on sterol response element binding proteins (SREBPs), which have a fungal ancestor conserved in S. pombe but not in S. cerevisiae (Butler, 2013). A comparative characterization of the regulated activation of SREBPs and Mga2/Spt23 in different fungi paired with comprehensive transcriptome analyses might prove extremely informative (Raychaudhuri et al, 2012). It is tempting to speculate that the increased complexity of fatty acid desaturases in mammals or Candida albicans compared to S. cerevisiae necessitates more complex networks of lipid and membrane sensors to coordinate fatty acid desaturation and sterol homeostasis (Oh and Martin, 2006).…”
Section: Mga2 and Spt23 As Key Regulators Of Membrane Fluiditymentioning
confidence: 99%
“…A coordinated regulation of fatty acid desaturation and sterol biosynthesis is common to all fungi and mammals (Goldstein et al, 2006;Osborne and Espenshade, 2009;Raychaudhuri et al, 2012). The transcriptional regulation in mammals relies on sterol response element binding proteins (SREBPs), which have a fungal ancestor conserved in S. pombe but not in S. cerevisiae (Butler, 2013).…”
Section: Mga2 and Spt23 As Key Regulators Of Membrane Fluiditymentioning
confidence: 99%